일본잎갈나무와 현사시나무를 이용한 브리켓의 제조 - 한규성; Gyu Seong Han; 김연일; Youn Il Kim; 문경태; Kyoung Tae Mun (목재공학, 2012)
바이오매스로부터의 고밀화연료는 북미와 유럽에서 신재생에너지로서 널리 이용되고 있다. 본 연구에서는 일본잎갈나무와 현사사나무를 피스톤 프레스를 이용하여 브리켓을 제조하였으며. 연료적 특성 및 고밀화 특성을 밝히고자 압력. 가압사간. 수종 및 목분 크기가 브리켓의 특성에 미치는 영향을 조사하였다. 상온에서 110, 170 MPa의 압력을 가해 제조된 일본잎갈나무와 현사시나무 브리켓의 4주간 경과 후의 밀도는 0.66~0.94g/cm3이고, 적정 가압시간은 12초이며, 제조 압력이 증가하면 브리켓의 밀도는 직선적으로 증가하였다. 일본잎갈나무 브리켓야 현사시나무 브랴켓보다 밀도가 컸으며, 목분의 크기가 클수록 브리켓의 밀도가 컸다. Densified fuels from biomass are widely used in North America and Europe as a regenerable and clean bioenergy. In this study, the fuel characteristics and densification characteristics of Japanese larch and Hyunsasi poplar were studied using a piston-type briquetting machine. The effects of pressure, pressure holding time, species, and particle size on briquette characteristics were studied. At room temperature, the highly densified briquettes of Japanese larch and Hyunsasi poplar can be produced at a compression pressure of 110~470 MPa. The produced briquettes have densities between 0.66 and 0.94 g/cm3 after 28 days of storage at room temperature, The optimum pressure holding time was found to be 12 seconds There is a linear increase in pressure with increase in density. The densities of briquettes from Japanese larch were higher than those of briquettes from Hyunsasi poplar. Also, the coarser particle size resulted in higher densities in briquettes than the finer particle size.